The oxidative-glycolytic balance influenced by sprint duration Is key during repeated sprint in hypoxia - Raberin, A.; Elmer, J.; Willis, S. J.; Richard, T.; Vernillo, G.; Iana, F. M.; Girard, O.; Malatesta, D.; Millet, G. P. (Medicine & Science in Sports & Exercise, 2023)
Purpose This study investigates the effects of normobaric hypoxia on repeated sprint exercise (RSE) with different balance between oxidative (phosphocreatine and oxidative pathway) and glycolytic contributions. Therefore, performance and psychophysiological responses were compared during RSE to exhaustion with the same exercise-to-rest ratio (1:2) but different sprint durations (5, 10, or 20 s) either in normoxic (RSN) or hypoxic (RSH; Fio2 = 0.13) conditions.